1993
DOI: 10.1007/bf00201343
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of indole-3-acetic acid in untransformed and Agrobacterium rhizogenes-transformed pea roots using gas chromatography mass spectrometry

Abstract: Abstract. Root segments of Pisum sativum L. were transformed by several strains of Agrobacterium rhizogenes. The resulting hairy roots, as well as apical segments from untransformed pea roots, were used to initiate root lines cultured in vitro. Levels of free IAA were quantified in the sub-cultured lines by gas-chromatography coupled to mass spectrometry, using selected ion monitoring. For most of the cultured untransformed and transformed root lines the IAA content was very small, compared with levels in untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
3
0
0
Order By: Relevance
“…Our results were consistent with data showing that hairy roots from bittersweet nightshade (Gartland et al, 1991) and pea (Schaerer and Pilet, 1993) and shoots from TL-DNAtransformed rape seed (Julliard et al, 1992) display normal levels of endogenous IAA. More specifically, our results agreed with the recent evidence that the expression of the 35s rolB gene in tobacco plants has no significant effect on either the endogenous levels of IAA (Nilsson et al, 1993;Schmiilling et al, 1993) or the rate of IAA metabolism or the in vivo hydrolysis of exogenously supplied IAA Glc ester (Nilsson et al, 1993).…”
Section: Dlscusslonsupporting
confidence: 92%
“…Our results were consistent with data showing that hairy roots from bittersweet nightshade (Gartland et al, 1991) and pea (Schaerer and Pilet, 1993) and shoots from TL-DNAtransformed rape seed (Julliard et al, 1992) display normal levels of endogenous IAA. More specifically, our results agreed with the recent evidence that the expression of the 35s rolB gene in tobacco plants has no significant effect on either the endogenous levels of IAA (Nilsson et al, 1993;Schmiilling et al, 1993) or the rate of IAA metabolism or the in vivo hydrolysis of exogenously supplied IAA Glc ester (Nilsson et al, 1993).…”
Section: Dlscusslonsupporting
confidence: 92%
“…The enhanced content of endogenous IAA in transgenic plants may be due to the expression of aux and rol genes of A. rhizogenes. Similar results were reported in Pisum sativum, where an agropine-type hairy root induced by A. rhizogenes strain 15834 contains significantly higher concentration of IAA than other transformed root lines and non-transformed roots (Schaerer and Pilet, 1992). They further reported that, the IAA content was very small in untransformed and transformed root lines, compared with the levels in untransformed intact primary roots.…”
Section: Endogenous Iaa Concentrationsupporting
confidence: 73%
“…The levels of free IAA in N and T roots of H. muticus are comparatively low. They are, however, in line with data published by Schaerer and Pilet (1993) where long term root cultures of Pisum sativum, rather than newly initiated ones, were studied. In spite of their growth rate and prolific branching, all hairy root lines except one had lower IAA levels than intact primary roots.…”
Section: Treatmentsupporting
confidence: 71%